The Role of Digital Marketing Strategies in Increasing Hamed Kebab Sales Turnover - Wahyuni, Lusi Tri (Universitas Nusantara PGRI Kediri, 2024)
Research aim: The aim of this research is to increase knowledge about digital marketing for MSMEs and how method increase turnover MSME sales ​ Design/Method/Approach: In this research, researchers used qualitative methods . With Technique interviews , observations And documentation . Object study This is the UMKM Kebab Hamed on Jl. Dahlia No.3, Mangunrejo, Tulungrejo, Kec. Pare, Kediri Regency. Research Finding: results study showing that Utilization of digital marketing in means promotion to enhancement turnover sale. Research limitations: Research limitations this is a lack of time in doing interviews because MSME product owners are difficult to find.